Employment and labour market dynamics : a review of Bangladesh's development, 2002 - Centre for Policy Dialogue (Bangladesh) (Dhaka : University Press, 2003)
Contributed articles.
"Centre for Policy Dialogue."
Includes statistical references.
Includes bibliographical references.
BIED
Complimentary copy from BIED
Keywords: Manpower policy -- Bangladesh; Manpower policy -- Bangladesh -- Statistics; Bangladesh -- Economic policy; Bangladesh -- Economic policy -- Statistics